IMPLEMENTASI SISTEM INFORMASI PENJUALAN TUNAI PADA UD. FN PERSADA TANGERANG DALAM MENINGKATKAN PENGELOLAAN STOK DAN LAPORAN PENJUALAN [IMPLEMENTATION OF A CASH SALES INFORMATION SYSTEM AT UD. FN PERSADA TANGERANG TO IMPROVE STOCK MANAGEMENT AND SALES REPORTING] - Pepi Permatasari; Sri Wahyuningsih (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
The sales activity of building materials plays a crucial role in the process of constructing houses and other infrastructure. However, in several building material supply stores, the sales mechanism is still carried out manually, requiring customers to visit the store in person to complete the purchase transaction (Rijal et al., 2024). Advances in science and technology have had an impact on company activities, particularly in data processing into information (Imannudin Akbar et al., 2023). To monitor sales activities, a good information system is needed to keep up with the rapidly growing business, especially due to the increasing number and value of transactions. This study analyzes and designs a sales application to facilitate transaction services. Primary data is obtained through observation of the existing system. Secondary data is analyzed through interviews with users and document review used in the transaction process. Secondary data, on the other hand, is obtained from literature studies and other sources, such as the internet. The system analysis and design are carried out with an object-oriented approach through UML (Unified Modeling Language) and structured database analysis. The expected outcome of this research is an application developed using the Java programming language with MySQL database support, which is expected to improve service efficiency in the sales process (Nistrina & Sahidah, 2022).